Polypropylene composition

CN117980352BActive Publication Date: 2026-10-27BASELL POLIOLEFINE ITALIA SRL
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202180102639.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-06
Publication Date
2026-10-27
Estimated Expiration
2041-10-06

Smart Images

  • Figure BDA0004753499810000061
    Figure BDA0004753499810000061
  • Figure BDA0004753499810000101
    Figure BDA0004753499810000101
Patent Text Reader

Abstract

A polypropylene composition comprising: A) 71 wt% to 91 wt% of a propylene homopolymer B) 5 wt% to 15 wt% of a copolymer of propylene with ethylene containing 18 wt% to 32.0 wt% of ethylene derived units; C) 4 wt% to 15 wt% of a copolymer of propylene with ethylene containing 75 wt% to 90.0 wt% of ethylene derived units.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to polypropylene compositions having high modulus, low haze, high impact strength and high melting point, suitable for producing injection molded articles requiring high transparency, high impact strength and high modulus at the same time. Background Technology

[0002] As is known, isotactic polypropylene possesses a superior combination of excellent properties, making it suitable for a very wide range of applications. To improve the aforementioned properties of the stereotactic homopolymerization method of propylene, one or more copolymerization steps or one or more monomers are introduced.

[0003] EP 603 723 relates to a polypropylene composition comprising:

[0004] A) 70 to 98 wt% crystalline propylene homopolymer, or propylene with ethylene and / or C4-C 10 A crystalline random copolymer of α-olefins containing 0.5 to 10 wt% ethylene and / or α-olefins (part A); and

[0005] B) 2 to 30 wt% ethylene with one or more C4-C 10 An elastomeric copolymer of α-olefins containing 60 to 85 wt% ethylene and partially soluble in xylene at 25°C.

[0006] (Part B);

[0007] The xylene-soluble portion of the composition in tetrahydronaphthalene at 25°C has an intrinsic viscosity range of 0.8 to 1.1 dl / g at 135°C.

[0008] A propylene composition comprising (by weight percentage): A) 60%-95% of a crystalline propylene copolymer containing

[0009] A) 2.0% to 10.0% of ethylene-derived units having a melting point ranging from 148°C to 160°C; wherein the melting temperature Tm is measured on the reactor polymer by DSC; B) 40% to 5% of an ethylene copolymer containing 70% to 85% of ethylene-derived units with an intrinsic viscosity ranging from 0.8 to 3 dl / g. However, for certain applications, such as polymer foams, products with different flowability combined with high melt strength are particularly desirable. It is known in the art to prepare said polymer by melt blending propylene polymer portions with different molecular weights or to prepare reactor blends of said portions in multi-step polymerization.

[0010] These documents focus on component A as a random propylene-ethylene copolymer.

[0011] The applicant discovered that it can improve the modulus and hexane-soluble content of this composition while maintaining good haze and impact properties. Summary of the Invention

[0012] This disclosure provides a polypropylene composition comprising:

[0013] A) 71 wt% to 91 wt% propylene homopolymer, which has:

[0014] - Includes the portion soluble in xylene at 25°C, ranging from 1.5 wt% to 4.0 wt%.

[0015] Melt flow rate from -60.0 to 110.0 g / 10 min (MFR L, according to ISO 1133, condition L, i.e. 230 °C and 2.16 kg load);

[0016] B) 5 wt% to 15 wt% of a copolymer of propylene and ethylene, containing 18 wt% to 32.0 wt% of ethylene-derived units;

[0017] The xylene-soluble fraction of A)+B) at 25°C ranges from 7 wt% to 15 wt%.

[0018] The intrinsic viscosity of the xylene-soluble fraction of A)+B) at 25°C ranges from 0.5 dl / g to 1.5 dl / g.

[0019] The content of ethylene-derived units in the xylene-soluble fraction of A)+B) at 25°C ranges from 12.3 wt% to 24 wt%, which is lower than the content of ethylene-derived units in component B).

[0020] C) 4 wt% to 15 wt% of a copolymer of propylene and ethylene, containing 75 wt% to 90.0 wt% of ethylene-derived units;

[0021] In the polypropylene composition:

[0022] The xylene-soluble fraction at 25°C ranges from 5.0 wt% to 14.0 wt%.

[0023] The content of ethylene-derived units in the xylene-soluble fraction at 25°C ranges from 26.0 wt% to 43.0 wt%.

[0024] The intrinsic viscosity of the xylene-soluble fraction at 25°C ranges from 0.5 dl / g to 1.5 dl / g.

[0025] and

[0026] - The polypropylene composition has at least two melting points, with a higher range of 156.0°C to 166.0°C and a lower range of 100.0°C to 135.0°C;

[0027] Melt flow rate (MFR L, according to ISO 1133, condition L, i.e. 230°C and 2.16 kg load) in the range of -35.0 to 95.0 g / 10 min.

[0028] The amounts of components A), B), and C) are 100 wt%. Detailed Implementation

[0029] This disclosure provides a polypropylene composition comprising:

[0030] A) 71 wt% to 91 wt%; preferably 75 wt% to 86 wt%; more preferably 78 wt% to 83 wt% of propylene homopolymer, having:

[0031] - The portion soluble in xylene at 25°C, comprising between 1.5 wt% and 4.0 wt%; preferably between 1.8 wt% and 3.8 wt%; more preferably between 2.0 wt% and 3.2 wt%;

[0032] Melt flow rate (MFR L, according to ISO 1133, condition L, i.e. 230°C and 2.16 kg load) ranges from 60.0 to 110.0 g / 10 min; preferably from 71 g / 10 min to 99 g / 10 min; more preferably from 75 g / 10 min to 89 g / 10 min.

[0033] B) 5 wt% to 15 wt%, preferably 7 wt% to 13 wt%, more preferably 8 wt% to 12 wt% of a copolymer of propylene and ethylene, containing 18.0 wt% to 32.0 wt%, preferably 20.0 wt% to 30.0 wt%; more preferably 22.0 wt% to 28.0 wt% of ethylene-derived units;

[0034] The xylene-soluble portion of A)+B) at 25°C ranges from 7 wt% to 15 wt%; preferably from 8 wt% to 13 wt%; more preferably from 9 wt% to 12 wt%.

[0035] The intrinsic viscosity of the xylene-soluble fraction of -A)+B) at 25°C ranges from 0.5 to 1.5 dl / g; preferably from 0.7 to 1.3 dl / g; more preferably from 0.8 to 1.2 dl / g.

[0036] The content of ethylene-derived units in the xylene-soluble fraction of A)+B) at 25°C ranges from 12.3 wt% to 24.0 wt%; preferably from 14.2 wt% to 22.5 wt%, more preferably from 15.8 wt% to 21.4 wt%, which is lower than the content of ethylene-derived units in component B).

[0037] C) 4 wt% to 15 wt%, preferably 6 wt% to 13 wt%; more preferably 8 wt% to 11 wt% of a copolymer of propylene and ethylene, containing 75.0 wt% to 90.0 wt%; preferably 78.0 wt% to 88.0 wt%; more preferably 79.0 wt% to 85.0 wt% of ethylene-derived units;

[0038] In the polypropylene composition:

[0039] - The xylene-soluble portion at 25°C, ranging from 5.0 wt% to 14.0 wt%; preferably 7.0 wt% to 13 wt%; more preferably 8.0 wt% to 12.0 wt%;

[0040] The content of ethylene-derived units in the xylene-soluble fraction at 25°C ranges from 26.0 wt% to 43.0 wt%; preferably from 28.0 wt% to 40.0 wt%; more preferably from 29.5 wt% to 36.2 wt%.

[0041] The intrinsic viscosity of the xylene-soluble portion at 25°C ranges from 0.5 dl / g to 1.5 dl / g; preferably from 0.7 dl / g to 1.3 dl / g; more preferably from 0.8 dl / g to 1.2 dl / g.

[0042] and

[0043] - The polypropylene composition has at least two melting points, the higher range being 156.0°C to 166.0°C; preferably 158.0°C to 165.0°C, more preferably 160.0°C to 164.0°C, and the lower range being 100.0°C to 135.0°C, preferably 111.0°C to 130.0°C; more preferably 115°C to 127°C;

[0044] - Melt flow rate (MFR L, according to ISO 1133, condition L, i.e. 230°C and 2.16 kg load), ranging from 35.0 to 95.0 g / 10 min; preferably from 40.0 to 70.0 g / 10 min; more preferably from 45.0 to 65.0 g / 10 min.

[0045] The amounts of components A), B), and C) are 100 wt%.

[0046] For the purposes of this disclosure, the term copolymer must be intended to refer to a polymer containing only two monomers (propylene and ethylene).

[0047] The compositions disclosed herein possess high modulus, low haze, high impact strength, and high melting point. This makes the compositions ideal for the production of molded articles such as injection molded articles, particularly for the production of thin-wall injection molded (TWIM) articles.

[0048] Preferably, the relationship (tensile modulus at 0°C × charpy) / haze is greater than 100, more preferably greater than 125; and even more preferably greater than 135. The tensile modulus, charpy at 0°C, and haze are measured as described in the example.

[0049] The tensile modulus ranges from 1100 MPa to 2000 MPa, preferably from 1200 MPa to 1800 MPa.

[0050] The polypropylene composition disclosed herein is prepared by a sequence of at least three stages of polymerization, wherein each subsequent polymerization stage is carried out in the presence of polymer material formed in the preceding polymerization reaction, wherein component (A) is typically prepared in at least one first polymerization stage, component (B) is typically prepared in at least one second polymerization stage, and component (C) is typically prepared in at least one third polymerization stage.

[0051] The polymerization method can be carried out in the gas and / or liquid phases, in continuous or batch reactors such as fluidized beds or slurry reactors. For example, the polymerization of propylene polymer (A) can be carried out in the liquid phase using liquid propylene as a diluent, while the copolymerization stages to obtain propylene copolymer portions (B) and (C) are carried out in the gas phase, without intermediate stages except for partial degassing of the monomer. Alternatively, all continuous polymerization stages can be carried out in the gas phase. The reaction time, temperature, and pressure of the polymerization steps are not critical, but the temperatures for preparing portions (A), (B), and (C) can be the same or different, typically from 50°C to 120°C. If polymerization is carried out in the gas phase, the polymerization pressure is preferably from 0.5 to 12 MPa. The catalytic system can be pre-contaminated with a small amount of olefin (prepolymerization). The molecular weight of the propylene polymer composition is adjusted using known modifiers such as hydrogen.

[0052] In the second and third stages of the particularly preferred polymerization method, propylene / ethylene copolymers (B) and (C) are produced in a conventional fluidized bed gas-phase reactor in the presence of the polymerizing materials and catalyst system from the aforementioned polymerization steps. The propylene polymer compositions of this disclosure can also be obtained by preparing copolymers (A), (B), and (C) separately, using the same catalyst and operating under substantially the same polymerization conditions as described above, followed by mechanical blending of the molten copolymers using conventional mixing equipment such as a twin-screw extruder.

[0053] Each polymerization stage is carried out in the presence of a highly stereoselective, multiphase Ziegler-Natta catalyst. The Ziegler-Natta catalyst suitable for preparing the propylene polymer compositions of this disclosure comprises a solid catalyst component containing at least one titanium compound having at least one titanium-halogen bond and at least one electron donor compound (internal donor), both supported on magnesium chloride. The Ziegler-Natta catalyst system also includes an organoaluminum compound as a necessary cocatalyst and an optional external electron donor compound.

[0054] Suitable catalyst systems are described in European patents EP45977, EP361494, EP728769, EP 1272533 and international patent application WO00163261.

[0055] The polypropylene compositions disclosed herein are preferably obtained by polymerizing propylene and ethylene at different stages in the presence of a catalyst system comprising products obtained by contacting the following components:

[0056] a) A solid catalyst component comprising magnesium halide, a titanium compound having at least one Ti-halogen bond, and at least one electron donor compound selected from succinates.

[0057] b) Aluminum hydrocarbon compounds

[0058] c) Optional external electron donor compound.

[0059] In the solid catalyst component (a), the succinate is preferably selected from the succinate of formula (I).

[0060]

[0061] Where groups R1 and R2 are the same or different from each other, and are C1-C 20 Straight-chain or branched alkyl, alkenyl, cycloalkyl, aryl, arylalkyl, or alkylaryl groups, optionally containing heteroatoms; and groups R3 and R4 may be the same or different from each other, and are C1-C2. 20 Alkyl, C3-C 20 cycloalkyl, C5-C 20 The compound is an aryl, aralkyl, or alkylaryl compound, provided that at least one of them is a branched alkyl group; the two asymmetric carbon atoms identified in the structure of formula (I) are (S, R) or (R, S) stereoisomers.

[0062] R1 and R2 are preferably C1-C8 alkyl, cycloalkyl, aryl, arylalkyl, and alkylaryl groups. Particularly preferred are compounds in which R1 and R2 are selected from primary alkyl groups, especially branched primary alkyl groups. Examples of suitable R1 and R2 groups are methyl, ethyl, n-propyl, n-butyl, isobutyl, neopentyl, and 2-ethylhexyl. Particularly preferred are ethyl, isobutyl, and neopentyl.

[0063] Particularly preferred are compounds in which the R3 and / or R4 groups are secondary alkyl groups such as isopropyl, sec-butyl, 2-pentyl, 3-pentyl or cycloalkyl groups such as cyclohexyl, cyclopentyl, cyclohexylmethyl.

[0064] Examples of the above compounds are pure (S,R) forms or mixtures thereof of diethyl 2,3-bis(trimethylsilyl)succinate, diethyl 2,3-bis(2-ethylbutyl)succinate, diethyl 2,3-dibenzylsuccinate, diethyl 2,3-dibenzylsuccinate, diisopropylsuccinate, diethyl 2,3-bis(cyclohexylmethyl)succinate, diethyl 2,3-diisobutylsuccinate, diethyl 2,3-dineopentylsuccinate, diethyl 2,3-dicyclopentylsuccinate, and diethyl 2,3-dicyclohexylsuccinate, optionally in racemic form.

[0065] As described above, catalyst component (a) further includes a titanium compound having at least one Ti-halogen bond and magnesium halide. Magnesium halide is preferably in the active form of MgCl2, which is widely known from patent literature as a support for Ziegler-Natta catalysts. Patents USP 4,298,718 and USP 4,495,338 first describe the use of these compounds in Ziegler-Natta catalysis. It is known from these patents that the active form of magnesium dihalide used as a support or co-support in the components of catalysts for olefin polymerization is characterized by an X-ray spectrum in which the intensity of the strongest diffraction line appearing in the spectrum of the inactive halide decreases and is replaced by a halogen whose maximum intensity is shifted at a lower angle relative to a stronger linear direction.

[0066] Preferred titanium compounds used in the catalyst composition of this disclosure are TiCl4 and TiCl3; in addition, Ti(OR) can also be used. n-y X y The trihalools, where n is the valence of titanium, y is a number between 1 and n-1, X is a halogen, and R is a hydrocarbon group having 1 to 10 carbon atoms.

[0067] Preferably, the catalyst component (a) has an average particle size of 15 to 80 μm, more preferably 20 to 70 μm, and even more preferably 25 to 65 μm.

[0068] The alkyl-Al compound (b) is preferably selected from trialkylaluminum compounds, such as triethylaluminum, tri-n-hexylaluminum, and tri-n-octylaluminum. Mixtures of trialkylaluminum with alkylaluminum halides, alkylaluminum hydrides, or alkylaluminum sesquichlorides (such as AlEt2Cl and Al2Et3Cl3) may also be used.

[0069] Preferred external electron donor compounds include silicon compounds, ethers, esters such as ethyl 4-ethoxybenzoate, amines, heterocyclic compounds, and particularly 2,2,6,6-tetramethylpiperidine, ketones, and 1,3-diethers. Another class of preferred external donor compounds is of formula R. a 5 R b 6 Si(OR7 ) c A silicon compound, wherein a and b are integers from 0 to 2, c is an integer from 1 to 3, and the sum of (a+b+c) is 4; R 5 R 6 and R 7 The external electron donor compound is optionally an alkyl, cycloalkyl, or aryl group having 1-18 carbon atoms and containing a heteroatom. Particularly preferred are methylcyclohexyldimethoxysilane, diphenyldimethoxysilane, methyl tert-butyldimethoxysilane, dicyclopentyldimethoxysilane, 2-ethylpiperidinyl-2-tert-butyldimethoxysilane, and 1,1,1-trifluoropropyl-2-ethylpiperidinyl-dimethoxysilane and 1,1,1-trifluoropropyl-methyl-dimethoxysilane. The amount of the external electron donor compound is such that the molar ratio between the organoaluminum compound and the electron donor compound is 5 to 500; preferably 5 to 400; more preferably 10 to 200.

[0070] The catalyst forming component can be contacted with a liquid inert hydrocarbon solvent such as propane, n-hexane or n-heptane at a temperature below about 60°C, preferably about 0 to 30°C, for about 6 seconds to 60 minutes.

[0071] The catalyst components (a), (b), and optionally (c) described above can be fed into the pre-contact vessel in an amount such that the weight ratio (b) / (a) is in the range of 0.1-10, and if compound (c) is present, the weight ratio (b) / (c) is a weight ratio corresponding to the molar ratio as defined above. Preferably, the components are pre-contacted at a temperature of 10 to 20°C for 1 to 30 minutes. The pre-contact vessel is typically a stirred tank reactor.

[0072] Preferably, the pre-contacted catalyst is then fed into a prepolymerization reactor where the prepolymerization step takes place. The prepolymerization step can be carried out in a first reactor selected from a circulating reactor or a continuous stirred tank reactor, and is typically carried out in the liquid phase. The liquid medium comprises liquid α-olefin monomers, optionally with the addition of an inert hydrocarbon solvent. The hydrocarbon solvent can be aromatic (e.g., toluene) or aliphatic (e.g., propane, hexane, heptane, isobutane, cyclohexane, and 2,2,4-trimethylpentane). If present, the amount of hydrocarbon solvent is less than 40 wt% relative to the total amount of α-olefins, preferably less than 20 wt%. Preferably, step (a) is carried out in the absence of an inert hydrocarbon solvent.

[0073] The average residence time in the reactor is typically 2 to 40 minutes, preferably 10 to 25 minutes. The temperature range is 10°C to 50°C, preferably 15°C to 35°C. These conditions allow for a prepolymerization degree preferably ranging from 60 to 800 g / g of solid catalyst component, more preferably 150 to 500 g / g of solid catalyst component. Step (a) is further characterized by a low concentration of solids in the slurry, typically in the range of 50 g to 300 g of solids per liter of slurry.

[0074] The polypropylene compositions disclosed herein may further include additives commonly used in the field of polyolefins, such as antioxidants, light stabilizers, nucleating agents, acid stabilizers, colorants, and fillers.

[0075] The polypropylene composition disclosed herein can be used to produce injection-molded articles.

[0076] The following embodiments are given for illustrative purposes and not for limiting the scope of this disclosure.

[0077] Example

[0078] Data for propylene polymer materials were obtained using the following methods:

[0079] melt flow rate

[0080] Measured according to ISO 1133 (230℃, 2.16kg).

[0081] Ethylene (C2) content determined by NMR

[0082] 13 C10 NMR spectra were obtained on a Bruker Av-600 spectrometer equipped with a cryoprobe, operated at 120 °C in Fourier transform mode at 160.91 MHz. Ethylene content was measured in the total composition. The ethylene content of component B) was calculated using the amount of component B) according to the following equation:

[0083] C 2tot =C 2B X wt% component B / 100.

[0084] The sample was dissolved in 1,1,2,2-tetrachloroethane-d2 at 120 °C with a concentration of 8 wt / v%. A 90° pulse was applied, with a 15-second delay between the pulse and the CPD to remove [the sample]. 1 H- 13 C-coupling was used to obtain each spectrum. 512 transients were stored in 32K data points using a spectral window of 9000Hz.

[0085] The peak of Sββ carbon at 29.9 ppm (according to "through 13 Monomer sequence distribution in ethylene-propylene rubber measured by C10 NMR. 3. Use of reaction probability mode (CJ Carman, RA Harrington, and CE Wilkes, Macromolecules, 1977, 10, 536) as an internal reference. The sample was dissolved at 120 °C in 1,1,2,2-tetrachloroethane-d2 at a concentration of 8 wt / v%. A 90° pulse was applied, with a 15-second delay between the pulse and the CPD to remove [the precipitate]. 1H- 13 C-coupling was used to obtain each spectrum. 512 transients were stored in 32K data points using a spectral window of 9000Hz.

[0086] The spectral distribution, triplet state distribution, and compositional assessment were performed according to Kakugo (“Carbon-13 NMR determination of monomer sequence distribution in ethylene-propylene copolymers prepared with δ-titanium trichloride-diethylaluminum chloride”, M. Kakugo, Y. Naito, K. Mizunuma, and T. Miyatake, *Macromolecules*, 1982, 15, 1150) using the following equations:

[0087] PPP=100Tββ / S PPE=100Tβδ / S EPE=100Tδδ / S

[0088] PEP=100Sββ / S PEE=100Sβδ / S EEE=100(0.25Sγδ+0.5Sδδ) / SS=Tββ+Tβδ+Tδδ+Sββ+Sβδ+0.25Sγδ+0.5Sδδ

[0089] The molar percentage of ethylene content is evaluated using the following equation:

[0090] E%mol = 100 * [PEP + PEE + EEE] The weight percentage of ethylene content is evaluated using the following equation:

[0091] 100*E%mol*MWE

[0092] E%wt.=E%mol*MWE+P%mol*MWP

[0093] Where P mol% is the molar percentage of propylene content, and MWE and MWP are the molecular weights of ethylene and propylene, respectively.

[0094] According to Carman (CJCarman, R.A. Harrington, and C.E. Wilkes, Macromolecules 1977; 10, 536), the product of reactivity ratios r1 and r2 is calculated as follows:

[0095]

[0096] The stereoregularity of the propylene sequence is determined by PPP mmT ββ (28.90-29.65ppm) and the entire T ββ The ratio of (29.80-28.37ppm) is calculated as mm content.

[0097] molar ratio of feed gas

[0098] Determined by gas chromatography.

[0099] Samples for mechanical analysis

[0100] Samples were obtained according to ISO 294-2.

[0101] Flexural modulus

[0102] Measured according to ISO 178.

[0103] Melting temperature, enthalpy of fusion and crystallization temperature

[0104] According to ISO 11357-3, the determination is performed on samples of 5 to 7 mg weight under an inert N2 flow at a scan rate of 20 °C / min, with both cooling and heating. Indium is used for instrument calibration.

[0105] Soluble and insoluble fractions of xylene at 25℃ (room temperature)

[0106] According to ISO 16 152, xylene-soluble substances; solution volume 250 ml, precipitate at 25°C for 20 minutes, with stirring (magnetic stirrer) for 10 minutes, and dry under vacuum at 70°C.

[0107] Intrinsic viscosity (IV)

[0108] The sample was dissolved in tetrahydronaphthalene at 135°C and then poured into a capillary viscometer.

[0109] The viscometer tube (Ubbelohde type) is surrounded by a cylindrical glass sleeve; the design allows for temperature control using a circulating thermostatic liquid.

[0110] The downward passage of the meniscus is timed by a photoelectric device. Passage of the meniscus in front of the upper lamp activates a counter with a quartz crystal oscillator. When the meniscus passes the lower lamp, the counter stops, and the outflow time is recorded; this is then converted into an intrinsic viscosity value.

[0111] Charpy impact strength

[0112] Charpy impact test according to ISO 179-1eA, e ISO 1873-2

[0113] Haze (on a 1mm plate)

[0114] According to the method used, a 5×5cm sample was cut into 1mm thick injection-molded plates, and the haze value was measured using a Gardner photometric unit connected to a Hazemeter UX-10 or an equivalent instrument with a GE1209 light source (with filter "C"). A reference sample with known haze was used to calibrate the instrument. The plate to be tested was prepared according to the following method.

[0115] A 75×75×1mm sheet is molded using a GBF Plastiniector G235190 injection molding machine with a capacity of 90 tons under the following processing conditions:

[0116] Screw speed: 120 rpm

[0117] Back pressure: 10 bar

[0118] Melting temperature: 260℃

[0119] Injection time: 5 seconds

[0120] Switch to maintain pressure: 50 bar

[0121] Phase 1: Maintain pressure: 30 bar

[0122] Second stage pressure: 20 bar

[0123] Maintain pressure curve: Phase 1, 5 seconds

[0124] Second stage 10 seconds

[0125] Cooldown: 20 seconds

[0126] Mold water temperature: 40℃

[0127] According to Embodiment 1 of the present invention

[0128] catalyst system

[0129] The Ziegler-Natta catalyst was prepared according to Example 5, lines 48-55 of European Patent EP728769. Triethylaluminum (TEAL) was used as a co-catalyst and dicyclopentyldimethoxysilane (DCPMS) as an external donor, with the weight ratios shown in Table 1.

[0130] Prepolymerization treatment

[0131] Before introducing it into the polymerization reactor, the above-mentioned solid catalyst component is prepolymerized by keeping it in a suspension of liquid propylene at 20°C for about 5 minutes before introducing it into the first polymerization reactor.

[0132] polymerization

[0133] The polymerization operation was carried out in a continuous mode in a series of four reactors, each equipped with a device to transfer the product from one reactor to an adjacent one. The first two reactors were liquid-phase reactors, and the third and fourth reactors were fluidized bed gas-phase reactors. Component (A) was prepared in the first and second reactors, component (B) in the third reactor, and component (C) in the fourth reactor.

[0134] Hydrogen is used as a molecular weight regulator.

[0135] The gas phase (propylene, ethylene, and hydrogen) is analyzed continuously by gas chromatography.

[0136] At the end of the operation, the powder is discharged and dried under a nitrogen stream.

[0137] The main polymerization conditions are reported in Table 1.

[0138] Table 1

[0139] TEAL / Solid Catalyst Component Weight Ratio 9.5 9.3 TEAL / DCPMS weight ratio 10 10 Liquid phase reactor Polymerization temperature ℃ 70 70 pressure Bar-g 38 38 Duration of stay minute 49 46 H2 feed molppm 5538 5839 First gas phase reactor Polymerization temperature ℃ 75 70 pressure -bar 16 13 Duration of stay min 31 58 C2 / (C2+C3) Mole ratio 0.076 0.70 H2 / C2 Mole ratio 0.829 0.592 Second gas phase reactor Polymerization temperature ℃ 80 - pressure -bar 13 - Duration of stay min 43 - C2 / (C2+C3) Mole ratio 0.702 - H2 / C2 Mole ratio 0.597 -

[0140] C2 = ethylene; C3 = propylene; H2 = hydrogen

[0141] Polymer characteristics are reported in Table 2.

[0142] Table 2

[0143] Component a) Split wt% 81 85 85 ethylene content wt% 0 3.2 0 MFR g / 10' 79 20 81 Xylene solubles at 25°C wt% 2.5 6 3.2 Component b) Split wt% 10 15 15 Ethylene content in component B) wt% 25.0 80 82.0 xylene-soluble substances (A) + B at 25°C Wt% 11.8 - - XSIV (intrinsic viscosity of XS) dl / g 1.0 - - The ethylene content in the soluble fraction of xylene (A) + B) wt% 19.0 - - - - Component C) - - Split wt% 9 - - Ethylene content in component C) wt% 82 - - - Properties of the composition - - Xylene solubles at 25°C wt% 13.7 - 13.7 MFR g / 10' 53 - 64 XSIV (intrinsic viscosity of XS) dl / g 1.03 1.2 1.05 Ethylene content in the soluble portion of xylene Wt% 10 - 64.4 tensile modulus MPa 1420 990 1950 Haze (1mm plate) % 23 16.4 25 Melting temperature ℃ 163.0-122.8 - 163.3-110.8 Charpy hits 23℃ <![CDATA[KJ / m 2 ]]> 4.4 - 2.1 Charpy impacts 0°C <![CDATA[KJ / m 2 ]]> 2.2 - 1.1

[0144] Comparative Example 2 is Example 1 of WO 2011 / 045194, in which the tensile modulus has been reported.

[0145] By comparing Example 1 and Comparative Example 3 in Table 2, it is clear that the haze is lower in the embodiments according to the invention, but the tensile modulus is still higher and the Charpy impact is higher. When comparing Example 1 with Comparative Example 2, it is clear that the haze is lower (in terms of tensile modulus).

[0146] This means that by using the polymer of Example 1, a more rigid structure can be obtained by maintaining a low haze value.

Claims

1. A polypropylene composition comprising: A) 71 wt% to 91 wt% propylene homopolymers, which have: - Includes the portion soluble in xylene at 25°C, ranging from 1.5 wt% to 4.0 wt%. Melt flow rate, MFR L, from -60.0 to 110.0 g / 10 min, measured according to ISO 1133 under condition L, i.e. 230 °C and 2.16 kg load; B) 5 wt% to 15 wt% of a copolymer of propylene and ethylene, containing 18 wt% to 32.0 wt% of ethylene-derived units; The xylene-soluble fraction of A) + B) at 25°C ranges from 7 wt% to 15 wt%. The intrinsic viscosity of the xylene-soluble fraction of A) + B) at 25°C ranges from 0.5 dl / g to 1.5 dl / g, as measured in tetrahydronaphthalene at 135°C; The content of ethylene-derived units in the xylene-soluble fraction of A) + B) at 25°C ranges from 12.3 wt% to 24 wt%, which is lower than the content of ethylene-derived units in component B). C) 4 wt% to 15 wt% of a copolymer of propylene and ethylene, containing 75 wt% to 90.0 wt% of ethylene-derived units; In the polypropylene composition: The xylene-soluble fraction at 25°C ranges from 5.0 wt% to 14.0 wt%. The content of ethylene-derived units in the xylene-soluble fraction at 25°C ranges from 26.0 wt% to 43.0 wt%. The intrinsic viscosity of the xylene-soluble fraction at 25°C ranges from 0.5 to 1.5 dl / g, as measured in tetrahydronaphthalene at 135°C. and - The polypropylene composition has at least two melting points, with the higher melting point ranging from 156.0°C to 166.0°C and the lower melting point ranging from 100.0°C to 135.0°C, the melting points being measured by DSC at a scan rate of 20°C / min according to ISO 11357-3. Melt flow rate, MFR L, in the range of -35.0 to 95.0 g / 10 min, measured according to ISO 1133 under condition L, i.e., 230 °C and 2.16 kg load. The amounts of components A), B), and C) are 100 wt%.

2. The polypropylene composition according to claim 1, wherein component A) ranges from 75 wt% to 86 wt%, component B) ranges from 7 wt% to 13 wt%, and component C) ranges from 6 wt% to 15 wt%.

3. The polypropylene composition according to claim 1, wherein component B) contains 20.0 wt% to 30.0 wt% of ethylene-derived units.

4. The polypropylene composition according to claim 1, wherein the xylene-soluble portion of A) + B) at 25°C ranges from 8 wt% to 13 wt%.

5. The polypropylene composition according to claim 1, wherein the content of ethylene-derived units in the xylene-soluble portion of A) + B) at 25°C ranges from 14.2 wt% to 22.5 wt%.

6. The polypropylene composition according to claim 1, wherein component C) contains 78.0 wt% to 88.0 wt% of ethylene-derived units.

7. The polypropylene composition according to claim 1, wherein the xylene-soluble portion at 25°C ranges from 7.0 wt% to 13 wt%.

8. The polypropylene composition according to claim 1, wherein the content of ethylene-derived units in the xylene-soluble portion at 25°C ranges from 28.0 wt% to 40.0 wt%.

9. The polypropylene composition according to claim 1, wherein the intrinsic viscosity of the xylene-soluble portion at 25°C ranges from 0.7 dl / g to 1.3 dl / g.

10. The polypropylene composition of claim 1, wherein the polypropylene composition has at least two melting points, the higher range being 158.0°C to 165.0°C and the lower range being 111.0°C to 130.0°C.

11. The polypropylene composition according to claim 1, wherein the melt flow rate, MFR L, according to ISO 1133, is in the range of 40.0 to 70.0 g / 10 min measured under condition L, i.e., 230°C and 2.16 kg load.

12. The polypropylene composition according to claim 1, wherein the content of ethylene-derived units in the xylene-soluble portion at 25°C ranges from 29.5 wt% to 36.2 wt%.

13. The polypropylene composition according to claim 1, wherein the xylene-soluble portion at 25°C ranges from 8.0 wt% to 12.0 wt%.

14. An injection-molded article comprising the polypropylene composition according to claim 1.

Citation Information

Patent Citations

  • Components and catalysts for the polymerization of olefins

    EP0045977A2

  • Components and catalysts for the polymerization of olefins

    EP0361494A2

  • Polypropylene compositions having good transparency and improved impact resistance

    EP0603723A1

  • Components and catalysts for the polymerization of olefins

    EP0728769A1

  • Catalyst components for the polymerization of olefins

    EP1272533A1